Enhancing the Physiological Performance and Nutrient Utilization Efficiency in Two Faba Bean Cultivars via Nano, Mineral, and Chitosan Fertilization - Sanussi Ahmad; Mohammed Elmahdi; Bilkess M. A. Salim (African Journal of Advanced Pure and Applied Sciences, 2026)
A field experiment was conducted during the 2024/2025 harvest season in Sebha, Libya, to evaluate the physiological performance and nutrient use efficiency of two faba bean (Vicia faba L.) cultivars, under fertilization treatments: control, recommended mineral NPK, nano NPK, chitosan, 50% nano NPK + 50% mineral NPK, mineral NPK + chitosan, and nano NPK + chitosan. A randomized complete block design with three replications was used during current study. Water content, chlorophyll content, relative growth rate (RGR), the utilization efficiency of nitrogen, phosphorus, and potassium were evaluated. The combined application of nano NPK + chitosan resulted in the highest improvement in most of the studied parameters across treatments. The imported cultivar consistently outperformed the local cultivar in all evaluated traits, exhibiting greater leaf water content (88% vs. 80%), chlorophyll concentration (48% vs. 41%), relative growth rate (66 vs. 56 g/g/day), nitrogen use efficiency (57 vs. 46 kg/kg), phosphorus use efficiency (28 vs. 22 kg/kg), and potassium use efficiency (54 vs. 46 kg/kg). Nano-fertilizers and chitosan significantly enhanced water retention, photosynthetic efficiency, growth, and nutrient utilization, with the imported cultivar showing higher responsiveness. The findings suggest that the integration of nano-fertilizers and chitosan is an effective strategy to improve faba bean productivity in semi-arid regions of North Africa.